Evaluation Using New Products Types of Superplasticizers (Type Glenium) and Its Effect on Workability and The Compressive Strength of Concrete in Medium Hot Weathers - Z. Hussein, Haitham (Anbar Journal of Engineering Sciences, 2012)
This research, an attempt is carried to explain the use of new products of superplasticizers type (Glenium) locally recent period used in normal concrete strength,espeacailly in precast concrete. and the effect of medium hot weather climates on compressive strength of normal concrete made with various percentages of Glenium dosages , and to evaluate the dosages on workability of fresh concrete. Concrete mixes with two types containing of Glenium, G51 and G21. and different dosages of Gelnium, namely 0.8 and 1.2 liter per 100 kg of cement and reduction in water quantity about 25% Five mixes are made with 90 specimens, each mix contains 18 cubes ,half of specimens are cured by moist curing in normal condition, the other half of specimens are exposed to temperatures of 40oC.which is transferred to moist medium of hot water. The properties which are covered in this work consist of workability which represented by slump test, and strength represented by compressive strength and ultrasonic pulse velocity(UPV) tests. It is obtained that using the two types of Gelnium will improve the slump about (157% to 183%) compared with reference mix .The concrete cured at medium hot weather condition, show improves in compressive about (19.2 to38.12%) at 3 days age. The use Glenium type 51 is to be more suitable for normal concrete works in medium hot weather .